2019
DOI: 10.1016/j.sopen.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal cavernous hemangioma: A rare tumor that mimics adrenal cortical carcinoma

Abstract: Background Adrenal cavernous hemangioma is a rare tumor with only 60 cases previously reported. The aim of this study was to determine the frequency and clinical significance of adrenal cavernous hemangioma at our institution. Methods A retrospective review of consecutive patients undergoing adrenalectomy from 1994 to 2018 was completed to determine the frequency of cavernous hemangioma, characterize the clinical presentation, imaging and pathologic features and review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…2 Most frequently, these adrenal cavernous hemangiomas are incidentally found on ultrasound and CT. Preoperatively, the diagnosis of adrenal cavernous hemangioma is challenging as it is difficult to differentiate from adenoma and adrenal cortical carcinoma. 4 CT scan shows a well demarcated mass with heterogeneous appearance. 3 Presence of calcification within the mass raises the possibility of a hemangioma but not specific, as other adrenal masses such as carcinoma and cysts may also exhibit this feature.…”
Section: Discussionmentioning
confidence: 99%
“…2 Most frequently, these adrenal cavernous hemangiomas are incidentally found on ultrasound and CT. Preoperatively, the diagnosis of adrenal cavernous hemangioma is challenging as it is difficult to differentiate from adenoma and adrenal cortical carcinoma. 4 CT scan shows a well demarcated mass with heterogeneous appearance. 3 Presence of calcification within the mass raises the possibility of a hemangioma but not specific, as other adrenal masses such as carcinoma and cysts may also exhibit this feature.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital or hereditary factors are usually involved in skin, brain, and liver hemangiomas. These benign tumors present diagnostic challenges as their non-specific imaging characteristics can encompass benign and malignant entities, mainly mimicking adrenocortical carcinomas (5). Specifically, heterogenous features such as calcifications, necrosis, and hemorrhage raise concern for adrenocortical carcinomas when assessing adrenal masses.…”
Section: Discussionmentioning
confidence: 99%
“…It was only indicated that the tumor was mildly enhanced. On imaging, ACH must be differentiated from adrenal schwannoglioma, adrenocortical carcinoma, and hepatic hemangioma [14,15]. e final diagnosis of ACH depends on histopathology.…”
Section: Discussionmentioning
confidence: 99%